2019
DOI: 10.1088/1361-6501/ab1f40
|View full text |Cite
|
Sign up to set email alerts
|

High-speed digital light source photocurrent mapping system

Abstract: High-resolution spatial characterization of photovoltaic devices and photodetectors can reveal local defects that can have a detrimental impact on the lifetime and performance of such devices. Photocurrent mapping methods can provide high-resolution measurements and characterization can be achieved under actual operating conditions. However, such methods usually require costly, complicated systems and possess limited measurement speed. In this work an optical system based on a digital micro-mirror device is us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…[ 15 ] It has been demonstrated that the use of a DMD can accelerate scanning by orders of magnitude because both spatial and temporal modulation can be applied with the same DMD setup, without the need of a lock‐in system. [ 16 ] The aforementioned systems provide some solutions for increasing measurement speed and simplifying current mapping systems.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 ] It has been demonstrated that the use of a DMD can accelerate scanning by orders of magnitude because both spatial and temporal modulation can be applied with the same DMD setup, without the need of a lock‐in system. [ 16 ] The aforementioned systems provide some solutions for increasing measurement speed and simplifying current mapping systems.…”
Section: Introductionmentioning
confidence: 99%